Effect of solvents on the RAFT polymerization of N-(2-hydroxypropyl) methacrylamide. (June 2019) - Pan, Xiangyu; Zhang, Fenming; Choi, Bonnie; Luo, Yanlong; Guo, Xiaofeng; Feng, Anchao; Thang, San H.
Graphical abstract: Highlights: Systemically investigate of HPMA polymerization via RAFT in various solvents. Poor control of HPMA RAFT polymerization in aprotic solvents is discussed. Advice is given to obtain well-controlled PHPMA via RAFT polymerization. Abstract: Poly(N-(2-hydroxypropyl) methacrylamide) (PHPMA) is a promising drug platform as it is non-immunogenic, biocompatible and hydrophilic polymer. It is the first copolymer-drug conjugates to be evaluated in clinical trials. However, it is challenging to obtain well-controlled PHPMA with high conversions via either ATRP or RAFT polymerization in most organic solvents. In this study, we systematically investigate the polymerization of HPMA via RAFT in various solvents using 4-cyano-4-(((ethylthio)thioxomethyl)thio)pentanoic acid as a chain transfer agent. Kinetic experiments demonstrated that the retardation was alleviated in aprotic solvents resulting in low conversions and poor controllability of the polymerization. Variable temperature analyses and molecular dynamic simulation proved the low conversion and poor control of PHPMA was attributed to the hydrogen bonding of the polymeric system and the theoretical results are consistent with our experimental observations.